Interspecific Variation in Morphology, Behavior, and Ecology among Three Praying Mantid Species Tenodera attenuata Stoll, 1937, Mantis religiosa Linnaeus, 1758, and Sphrodromantis transcaucasica Stoll 1937 from District Mirpurkhas, Sindh, Pakistan (Journal of Medical & Health Sciences Review, 2025)
Mantids (Mantodea: Mantidae) are vital predatory insects in agroecosystems, yet their distribution and morphological variation remain poorly understood in Pakistan. This study aimed to address this knowledge gap by collecting (275) individuals of three mantid species including Tenodera attenuata, Mantis religiosa, and Sphodromantis transcaucasica from seven major Taluka's of district Mirpurkhas between May and November 2022-2023. Morphological traits, including body and pronotum length, were measured, and sex was determined via genitalia and abdominal segmentation. One-way ANOVA revealed significant differences in total body length between males and females (F= 3234.10, P